Qualidade estrutural em latossolos compactados cultivados com milho - Rossetti, Karina de Vares [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The purpose of this study was to evaluate the structural behavior of an Haplustox (LVd) and of an Eutrustox (LVef) after tractor-induced compaction based on soil physical properties and their relations with root growth and maize yield. The field experiments were carried out in two growing seasons (years I and II), in a randomized block design with split plots and four replications. The main treatments consisted of five compaction levels (T0, T1, T2, T3 e T4) and the secondary treatments of soil layers. The soil physical properties aggregate stability, bulk density, macro-and micro porosity, water retention, S index, penetration resistance, and the least limiting water range (RLL) were evaluated. In the first year, most S values of LVef exceeded 0.035, with the exception of T4 (passing a 10-ton tractor 3x), with 0.026. This index is not considered reliable to characterize the structural quality in relation to maize yield (Chapter 2). In the second year, the highest frequency of bulk density above the critical threshold for soil density occurred from T1 (passing a 4-ton tractor twice) to T4 (passing a 10-ton tractor 4x) (LVd) and from T2 (passing a 2-ton tractor 4x) to T4 (LVef) for critical soil resistance to penetration (cPR) 2 MPa. Without however reducing maize yield. The determination of RLL was effective to identify degradation, and regardless of the cPR value, the maize yield of LVd was more limited than that of LVef, (Chapter 3). For LVef, the responses in geometric mean diameter indices, mean weight diameter and percentage of aggregate diameter > 2.0 mm were similar in T0 (no additional compaction) as well as in the other treatments with induced compaction and higher than those of the LVd in terms of absolute values. Under the conditions of T0 (conventional tillage, no additional compaction), the reduction in macroporosity in LVd from 0.19 to 0.15 m3 m-3 had a positive influence on maize root length (Chapter 4)

O objetivo desse trabalho foi avaliar o comportamento estrutural em LATOSSOLO VERMELHO Distrófico (LVd) e LATOSSOLO VERMELHO Eutroférrico (LVef) após a compactação induzida por tratores, por meio de atributos físicos do solo e associá-los ao crescimento radicular e à produtividade da cultura do milho. Os experimentos foram conduzidos em campo por dois anos agrícolas (anos I e II), em delineamento em blocos casualizados em parcelas subdivididas, com quatro repetições cujos tratamentos principais consistiram de cinco condições de compactação (T0, T1, T2, T3 e T4) e os secundários por camadas de solo. Foram avaliados os atributos físicos do solo como a estabilidade de agregados, densidade, macro e microporosidade, retenção de água, índice S, resistência do solo à penetração e o intervalo hídrico ótimo (IHO). Para o LVef no ano I, a maioria dos valores do índice S situaram acima de 0,035 com exceção do T4 (três passadas do trator de 10 t) com 0,026. O índice S não é considerado um atributo confiável para caracterizar a qualidade estrutural em relação à produtividade de milho (Capítulo 2). No ano II, a maior frequência de densidade do solo maior que a densidade do solo crítica ocorreu no T4 (quatro passadas do trator de 10 t) (LVd) e no T2 (quatro passadas do trator de 4 t) ao T4 (LVef) na resistência do solo à penetração crítica (RPc) de 2 MPa. Porém não correspondeu em decréscimo da produtividade de milho. Neste aspecto, pode-se verificar que a determinação do IHO foi eficiente e complementar na identificação de condições mais favoráveis no LVef para o desenvolvimento do milho em relação ao LVd (Capítulo 3). Para a condição no LVef no ano II, os índices diâmetro médio geométrico, o diâmetro médio ponderado e a porcentagem de agregados maiores que 2,0 mm de diâmetro apresentaram respostas semelhantes tanto para o T0 (preparo convencional sem compactação adicional) como para...
Keywords: Milho; Fisica do solo; Latossolos; Produtividade agrícola; Milho - Raizes; Solos - Compactação; Soil physics